Listeria monocytogenes antagonizes the human GTPase Cdc42 to promote bacterial spread - Rigano, Luciano A. (2014)
The bacterial pathogen Listeria monocytogenes uses actin-based motility to spread from infected human cells to surrounding healthy cells. Cell-cell spread involves the formation of thin extensions of the host plasma membrane (‘protrusions’) containing motile bacteria. In cultured enterocytes, the Listeria protein InlC promotes protrusion formation by binding and antagonizing the human scaffolding protein Tuba. Tuba is a known activator of the GTPase Cdc42. In this work, we demonstrate an important role for Cdc42 in controlling Listeria spread. Infection of the enterocyte cell line Caco-2 BBE1 induced a decrease in the level of Cdc42-GTP, indicating that Listeria downregulates this GTPase. Genetic data involving RNA interference indicated that bacterial impairment of Cdc42 may involve inhibition of Tuba. Experiments with dominant negative and constitutively activated alleles of Cdc42 demonstrated that the ability to inactivate Cdc42 is required for efficient protrusion formation by Listeria. Taken together, these findings indicate a novel mechanism of bacterial spread involving pathogen-induced downregulation of host Cdc42.